A Compromise Programming to Task Assignment Problem in Software Development Project - Son, N.T. (Tech Science Press, 2021)
The scheduling process that aims to assign tasks tomembers is a difficult job in project management. It plays a prerequisite role in determining the project's quality and sometimes winning the bidding process. This study aims to propose an approach based on multi-objective combinatorial optimization to do this automatically. The generated schedule directs the project to be completed with the shortest critical path, at the minimum cost, while maintaining its quality. There are several real-world business constraints related to human resources, the similarity of the tasks added to the optimizationmodel, and the literature's traditional rules. To support the decision-maker to evaluate different decision strategies, we use compromise programming to transform multiobjective optimization (MOP) into a single-objective problem. We designed a genetic algorithm scheme to solve the transformed problem. The proposed method allows the incorporation of the model as a navigator for search agents in the optimal solution search process by transferring the objective function to the agents' fitness function. The optimizer can effectively find compromise solutions even if the user may or may not assign a priority to particular objectives. These are achieved through a combination of nonpreference and preference approaches. The experimental results show that the proposed method worked well on the tested dataset. Â© 2021 Tech Science Press. All rights reserved.